A biphasic, demineralized, and Decellularized allograft bone‐hydrogel scaffold with a cell‐based BMP‐7 delivery system for osteochondral defect regeneration. Issue 9 (9th May 2020) - Sun, Jiachen; Lyu, Jingtong; Xing, Fei; Chen, Ran; Duan, Xin; Xiang, Zhou
Abstract: The reconstruction of bone and cartilage defects remains a challenge in orthopedics and tissue engineering. In this study, a mimetic natural scaffold based on a demineralized and decellularized bone and collagen type I (Col I) allograft was developed. The resulting hydrogel has the capability of loading allogeneic bone marrow mesenchymal stem cells (BMSCs) resulting in the sustained release of bone morphogenetic protein‐7 (BMP‐7). BMSCs transfected with lentivirus loaded with BMP‐7 gene were used as the BMP‐7 delivery system, and then seeded on a demineralized and decellularized allograft bone‐collagen biphasic scaffold to enhance bone and cartilage regeneration. The results indicated that, after transfection, BMSCs had a higher expression of the BMP‐7 gene and the sustained release of BMP‐7 lasted more than 28 days. The preliminary biphasic scaffold promoted cell adhesion and proliferation. After implanting the transfected cells into the knee joints of beagle dogs, enhanced osteochondral defect regeneration was identified at 12 weeks postimplantation. Our results revealed that the new cell‐loaded scaffold can avoid the side effects and the short half‐life of BMP‐7, and promote the reconstruction of bone and cartilage defects. Such a composite system, therefore, shows potential in bone and cartilage tissue engineering applications.